The Effect of the Covid-19 Pandemic on Bangka Belitung Province Small and Medium Industry using Descriptive Statistics – Correlation and Multiple Linear Regression - Selani Satila; Dino Caesaron; Soemedi Hadiyanto; Erin Haynes (School of Industrial and System Engineering, Telkom University, 2021)
This study discusses how the COVID-19 pandemic affects all industrial sectors in Bangka Belitung,especially Small and Medium Industry (IKM) actors. The prolonged pandemic condition has forced IKMBangka Belitung players to lose up to 70% of their income due to the decline in people's purchasing power.Further analysis is needed regarding the impact of the COVID-19 pandemic on IKM Bangka Belitung,considering that this sector contributes 99% of all industrial sectors of the total business units totaling20,403 units, with a workforce absorption of 45,351 people. The sampling method was by distributingquestionnaires to 437 IKM actors in Bangka Belitung. The questionnaire was distributed to get the level ofimportance as primary data which was processed using descriptive statistics, pearson correlation and linearregression to see the contribution of each variable that could affect the performance of SMEs. The findingsfrom this study can be used as material for targeted and measurable policy making for the IKM BangkaBelitung Trustees agency, to formulate strategic steps in empowering IKM during the COVID-19pandemic.